2018
DOI: 10.1016/j.jsxm.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity, Sexual Dysfunction, and Sexual Life Quality Among Psychiatric Hospital Inpatients With Schizophrenia

Abstract: Background Sexual dysfunction occurs commonly in patients with psychiatric illness and may be related to the primary mental disorder, comorbidity with sexual disorders or medical illness, or medications used for mental disorders treatment, but the magnitude of this problem is unknown. Aim To estimate the prevalence of current sexual activity, sexual dysfunction, and sexual attitude and influence of factors on patients with sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
1
20
0
4
Order By: Relevance
“…They also tend to experience greater dysfunction in multiple areas of sexual functioning, exhibiting lower sexual self-esteem, motivation, and satisfaction, and higher sexual anxiety, depression, and fear than women without a psychiatric diagnosis (Huguelet et al, 2015). Women with psychotic disorders also tend to report greater sexual dysfunction and lower levels of sexual interest than their male counterparts (Driscoll, 2010; Incedere & Küçük, 2017; Ma et al, 2018), a finding that might in part be explained by women’s increased exposure to emotional and sexual abuse (Huguelet et al, 2015; Matevosyan, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also tend to experience greater dysfunction in multiple areas of sexual functioning, exhibiting lower sexual self-esteem, motivation, and satisfaction, and higher sexual anxiety, depression, and fear than women without a psychiatric diagnosis (Huguelet et al, 2015). Women with psychotic disorders also tend to report greater sexual dysfunction and lower levels of sexual interest than their male counterparts (Driscoll, 2010; Incedere & Küçük, 2017; Ma et al, 2018), a finding that might in part be explained by women’s increased exposure to emotional and sexual abuse (Huguelet et al, 2015; Matevosyan, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The intimate relationship functioning of people with a psychotic disorder was consistently lower than that of healthy controls and individuals with other psychiatric conditions. Although quality of life may be higher among people with psychotic disorders who are married, marriage and cohabitation rates tend to be low in this population, especially for those with an earlier age of onset (Ma, Chao, Hung, Sung, & Chao, 2018;Nyer et al, 2010;Stewart et al, 2013). Stigma, social withdrawal, and limited social worth may all contribute to this phenomenon (Stewart et al, 2013).…”
Section: Marital and Sexual Functioningmentioning
confidence: 98%
“…[23] The varying prevalence rates can be explained by the differences in sample selection and assessment criteria. [151617] In contrast to this study which used the DSM-IV TR diagnostic criteria, previous studies used questionnaires to assess sexual functioning. The mechanical use of assessment instruments may have resulted in higher rates, as these often do not take into account the distress and broader personal and social context that are necessary for a contextual diagnosis of sexual dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Olfson's study showed that schizophrenic patients with current sexual dysfunction showed signi cantly poorer global QoL and less satisfaction enjoyment in their lives when compared to patients without current sexual dysfunction [6]. Ma's study also points out quality of sexual life and sexual dysfunction on PwS are associated with interactions among psychological, sociological, and biochemical-pharmacological factors [7].…”
Section: Introductionmentioning
confidence: 99%